(untitled) (Eurasian Medical Research Periodical, 2023)
In the last 20 years, viral infectious diseases have become the most urgent problem in medicine. Severe acute respiratory syndrome (SARS-nCoV) in 2002, Ebola disease in Africa in 2014, Middle East coronavirus syndrome (MERS-CoV) in 2015, and Zika fever in 2016 can be examples [3]. The coronavirus infection caused by SARS-CoV-2 caused a pandemic, unlike previous diseases, and once again proved the need for indepth study of these diseases.